Upaya Edukasi Ibu Hamil Dalam Mengenali Kurang Energi Kronis (KEK) Melalui Faktor Risiko - Oon Fatonah Akbarini; Asmaurika Pramuwidya; Lepita Lepita (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Chronic Energy Deficiency is a condition of a person's nutritional status which is caused because the source of intake they receive does not meet their daily and sustainable needs. The nutritional needs of pregnant women have increased and if this is not met in the short and long term it can result in chronic energy deficiency. The aim of this research is to determine the mother's level of knowledge in detecting CED. Based on the results of the Chi Square test, it was found that the value of p = 0.000 < α (0.05) for the variables of pregnancy distance and income showed that there was a significant relationship that influenced the incidence of chronic energy deficiency (CED) in pregnant women, while the variables of parity, education and employment showed that there was none. significant relationship that influences the incidence of chronic energy deficiency (CED) in pregnant women. The results of the activity showed that the activity to increase knowledge of pregnant women in detecting chronic energy deficiency (KEK) through risk factors in the Saigon City Health Center area, Pontianak City, ran smoothly. There was an increase in knowledge of pregnant women between before and after being given counseling by 20 points.